Phenotype onset in Huntington's disease knock‐in mice is correlated with the incomplete splicing of the mutant huntingtin gene. Issue 12 (7th July 2019) - Franich, Nicholas R.; Hickey, Miriam A.; Zhu, Chunni; Osborne, Georgina F.; Ali, Nadira; Chu, Tiffany; Bove, Nicholas H.; Lemesre, Vincent; Lerner, Renata P.; Zeitlin, Scott O.; Howland, David; Neueder, Andreas; et al.
Abstract: Huntington's disease (HD) is a progressive neurodegenerative disorder caused by an expanded CAG repeat within the huntingtin ( HTT ) gene. The Q140 and Hdh Q150 knock‐in HD mouse models were generated such that Hdh Q150 mice have an expanded CAG repeat inserted into the mouse Htt gene, whereas in the Q140s, mouse exon 1 Htt was replaced with a mutated version of human exon 1. By standardizing mouse strain background, breeding to homozygosity and employing sensitive behavioral tests, we demonstrate that the onset of behavioral phenotypes occurs earlier in the Q140 than the Hdh Q150 knock‐in mouse models and that huntingtin (HTT) aggregation appears earlier in the striata of Q140 mice. We have previously found that the incomplete splicing of mutant HTT from exon 1 to exon 2 results in the production of a small polyadenylated transcript that encodes the highly pathogenic mutant HTT exon 1 protein. In this report, we have identified a functional consequence of the sequence differences between these two models at the RNA level, in that the level of incomplete splicing, and of the mutant exon 1 HTT protein, are greater in the brains of Q140 mice. While differences in the human and mouse exon 1 HTT proteins (e.g., proline rich sequences) could also contribute to the phenotypic differences, our data indicate that the incomplete splicing of HTT and approaches to lower the levels of the exon 1 HTT transcript should be pursued as therapeutic targets. Abstract :